Continuous-flow nitration of o-xylene: effect of nitrating agent and feasibility of tubular reactors for scale-up - Sharma, Y.; Joshi, Ramesh A.; Kulkarni, A. A. (Organic Process Research & Development, 2015)
Continuous-flow nitration of o-xylene has been studied with different nitrating agents over a wide range of conditions for different parameters such as temperature, residence time, and concentrations. A nitrating mixture comprising sulfuric acid and fuming nitric acid was seen to yield higher selectivity for the isomer 1,2-dimethyl-3-nitrobenzene over the isomer 1,2-dimethyl-4-nitrobenzene and also a non-negligible quantity of dinitro derivatives of o-xylene. With only fuming nitric acid as the nitrating agent, the reaction was selective for 1,2-dimethyl-4-nitrobenzene over 1,2-dimethyl-3-nitrobenzene. Impurities mainly come from nitration of mononitro derivatives, and this occurs more from nitration of the 3-nitro isomer because of its higher reactivity with nitric acid. An economic analysis of the continuous-flow reactor for the production of 1,2-dimethyl-4-nitrobenzene at 100 and 500 kg/h in a jacketed tubular reactor showed that numbering-up is a more economical approach for higher production capacity. A combination of large- and small-sized tubes depending upon the relative rates of heat generation during a reaction will achieve more profit and a shorter payback period than having the entire reactor made of a single tube size.

Continuous flow telescopic oxidation of alcohols via generation of chlorine and hypochlorite - Sharma, Y.; Moolya, S.; Joshi, Ramesh A.; Kulkarni, Amol A. (Reaction Chemistry & Engineering, 2017)
A 3-step continuous flow oxidation of alcohols is demonstrated with continuous generation of chlorine as the first step followed by its use for the flow synthesis of high strength sodium hypochlorite. The solution is subsequently used for oxidation of alcohols in the presence of a catalytic amount of the nitroxyl radical “TEMPO”, which inhibits oxidation at the aldehyde stage. Selective oxidations of eight different alcohols were demonstrated. To achieve identical yields, the aromatic alcohols containing electron withdrawing groups needed a longer residence time than aliphatic alcohols.